Efforts of The Health Quarantine Center in Monitoring Environmental Pollution at The Port - Wulan Syafina (Inspire Global Insight Journal, 2026)
This study was motivated by the increasing risk of environmental pollution in domestic port areas, which can affect the health of port communities. As the authority responsible for port environmental health, the Health Quarantine Office (BKK) plays a crucial role in supervising and preventing potential pollution. This study aims to analyze the efforts of the Health Quarantine Office Class I Tanjung Balai Karimun in monitoring environmental pollution in domestic ports and to evaluate the effectiveness of its environmental monitoring activities. The research employed a descriptive qualitative approach, with data collected through field observations, in-depth interviews, and documentation involving BKK officers and port management personnel. Data analysis was conducted using data reduction, data display, and conclusion drawing techniques to describe the process and outcomes of the environmental supervision activities. The findings revealed that BKK conducted monitoring activities such as water quality inspection, ship waste control, sanitation inspection of port facilities, and environmental awareness education for port users. However, the supervision activities still face challenges, including limited human resources, laboratory facilities, and irregular monitoring schedules. This study contributes to a broader understanding of the BKK's role not only in human health protection but also in environmental pollution control at domestic ports. The results are expected to serve as a basis for strengthening integrated environmental monitoring policies in domestic ports.